Validation of the Grief Support in Healthcare Scale among frontline nursing professionals working in COVID-19 inpatient wards in Korea - Ahn, Junseok; Bang, Young Rong; Cho, Eulah; Ahmed, Oli; Kim, Jeong Hye; Hong, Youjin; Chung, Seockhoon; Anderson, Keith A. (Frontiers in Psychiatry, 2023)
During the COVID-19 pandemic, healthcare workers (HCWs) have been exposed to higher levels of anxiety and psychological stress. Nurses who cared for COVID patients could not avoid repeated mourning as they witnessed the deaths of their patients. Therefore, tools are needed to evaluate whether there is adequate support for the grieving process of HCWs. Data from 229 nurses who witnessed the deaths of COVID-19 inpatients were analyzed using an online survey of 339 nurses working in three tertiary hospitals. Factor analysis was conducted to validate the 10-item Korean Grief Support in Health Care Scale (GSHCS). Stress and anxiety to viral epidemics-9 was used to measure stress and anxiety caused by coronavirus, generalized anxiety disorder-7 was used to measure overall anxiety, and patient health questionnaire-9 was used for depression. Convergent validity correlation analysis was also performed with GSHCS. The two-factor model showed a good fit for the 10-item GSHCS (χ2 = 35.233, df = 34, p-value = .410, CFI = .999, TLI = .990, RMSEA = .013, SRMR = .064). Cronbach's alpha is 0.918 and McDonald's omega is 0.913, suggesting that the 10-item version of the GSHCS is reliable for determining psychometric properties. The 10-item Korean version of the GSHCS is a reliable and valid measure of psychological support for grief among frontline nursing professionals who have witnessed the deaths of their patients. A two-factor model of the GSHCS has a good model fit and good convergent validity with other rating scales that measure viral anxiety, depression, and general anxiety.